Proses Metakognitif dalam Pengajuan Masalah Geometri Berdasarkan Gaya Kognitif Field Dependent dan Field Independent - Yuli Suhandono (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2017)
This study aimed to describe about metacognitive process of student in geometry problem posing based cognitive style Field Dependent (FD) and Field Independent (FI). The subjects were four students of grade X. The result showed that metacognitive process of subjects FD and FI first category in posing geometry problem, doing activity of planning, monitoring and evaluating process and the result thinking about every step of problem posing. Metacognitive process of subject FD of second category in posing geometry problem, doing activity of planning, monitoring, and evaluating process and the result thinking about step understanding information, arranging the planning of problem posing and formulating problem. Furthermore, metacognitive process of subject FI second category in posing geometry problem, doing of planning activity, monitoring and evaluating process and the result thinking about step understanding information, arranging the planning of problem posing and controlling back of suitability problem made with first information